Spectrum of Biopsy Proven Primary Tubulointerstitial Diseases of the Kidney: A Single Centre Study - Wani, Asif Sadiq; Zahir, Zafirah; Krishnani, Narendra (Journal of Drug Delivery and Therapeutics, 2022)
Background: The tubulointerstitial diseases can be due to a wide variety of etologies and mechanisms which vary with age, race and geographical area. In this study we aim to study the clinicopathological spectrum of biopsy proven primary tubulointerstitial diseases among patients in North India. Methods: This is a 5 year retrospective, single centre cohort, observational study.The data base was searched to identify all patients with primary tubulointerstitial diseases in their native kidney biopsies. Results: A total of 3091 renal biopsies were studied of which 283 were primary tubulointerstitial diseases. The mean age of patients was 43.2 (±14.6) years. Most of the patients were males with acute kidney injury as the most common presentation. Tubulointerstitial nephritis was the most common disease occurring in 126 patients. Acute interstitial nephritis was seen in 81 patients and chronic interstitial nephritis was seen in 45 patients. Granulomatous interstitial nephritis was seen in 27 patients. There were four patients of pigment nephropathy, 83 cases of acute tubular necrosis and 19 cases of cast nephropathy. Conclusion: Primary tubulointerstitial diseases comprise about 9.1% of the total cases. Tubulointerstitial nephritis is the most common diagnosis in these patients. Tuberculosis is still a leading cause of granulomatous interstitial nephritis in our country followed by fungal etiology. Acute cortical necrosis affects mostly females post obstretric complications in our setup. Given the enemic nature of malaria in India, G-6PD deficiency is an important differential in patients presenting with pigment nephropathy. Keywords: Biopsy, Tubulointerstitial Diseases of the Kidney, Tuberculosis, Acute cortical necrosis